HEALTHCARE WAQF AND SOCIO-ECONOMIC DEVELOPMENT IN INDONESIA: CASE STUDY OF HOSPITAL ROEMANI MUHAMMADIYAH - Rahmanto, Mukhlis; Ab Rahman, Asmak; Mohd Daud, Zaidi (Jurnal Syariah, 2023)
The article describes a waqf-based hospital in Indonesia to show continuity and change in the development of waqf-based Islamic hospitals, which began in the Prophetic era and has survived until today. The findings show there are several transformations from waqf-based hospitals in medieval and early modern Islam where many of the founders, from the Sultan and the elites of the Islamic dynasty to the donors, come from the civil and private sector, for instance, Ḥājj Roemani, the founder of Hospital Roemani Muhammadiyah, an entrepreneur with the same background as Hakim Muhammad Said of Hamdard Pakistan. Also, there is a shift from what is called "free healthcare service to the needy and poor", which is generally understood as fully free, to the several features of changes ranging from a very nominal charge, reduction of the cost, and health insurance with low premiums subsidized by the state for the needy and poor. The shifting influence of the hospital management model towards a commercial, even though the hospital itself is waqf based, whose essential character is non-profit. We argue this is due to the human population growth and the challenges of the emergence of various diseases until the pandemic, increasing the need for health funds. Hence, the hybrid scheme of Islamic philanthropy funds is needed and can make this hospital an institution that not only plays a role in the socio-economic development in the health sector but extends to other socio-economic sectors.